Behavioural beliefs of Ghanaian radiographers and reporting of child physical abuse. Issue 1 (February 2019) - Antwi, W.K.; Reeves, P.; Ferris, C.; Aziato, L.
Abstract: Introduction: Radiographers are well placed to flag non accidental injury in children due to their unique position within the imaging chain. Being able to identify (or suspect) physical abuse in children and reporting the incident are, however, two different issues. This study was conducted to explore the external influences in the decision making of the Ghanaian radiographer to report suspected child physical abuse (CPA). Method: This was a qualitative study which applied interpretive phenomenology. Semi-structured interviews were conducted with 20 radiographers who were selected from various hospitals throughout the ten regions of Ghana using purposive sampling. Data was thematically analysed and managed with NVivo Version 10. Themes developed formed the basis of this discussion. Results: Several socio-cultural beliefs and behaviours impacted on the Ghanaian radiographers' decisions to report suspected child physical abuse. The findings of this study indicated that cultural solidarity, superstition and police frustrations were among other factors that characterised the Ghanaian radiographer's inability to report child physical abuse when it occurred. Conclusion: Radiographers reported fear of both physical and spiritual attack when child physical abuse was reported. This paper argues that, to achieve the fight against child physical abuse in some African countries such as Ghana, radiographers would have to be educated and counselled against belief in superstition and adherence to some cultural values which affect child protection. Highlights: Radiographers' barriers to reporting child physical abuse were explored. Socio-cultural beliefs impacted on radiographers' decisions to report. Cultural solidarity characterised reporting of child physical abuse. Superstition and fear of physical attacks hindered reporting. Education and counselling regarding cultural beliefs would promote reporting.